2023
DOI: 10.3390/math11010215
|View full text |Cite
|
Sign up to set email alerts
|

Dual Solutions of Unsteady Mixed Convection Hybrid Nanofluid Flow Past a Vertical Riga Plate with Radiation Effect

Abstract: A mathematical model for the unsteady, two-dimensional mixed convection stagnation point flow over a Riga plate is presented in this study. Convective boundary conditions, time-dependent derivatives, mixed convection, radiation effects, and the Grinberg term were all incorporated into the formulation of the governing equations and boundary conditions. By incorporating similarity transformations, ordinary differential (similarity) equations (ODEs) are derived from the partial differential equations (PDEs) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…They reported that mixed convection had proliferated the microorganism transfer rate and the y$y$‐direction flow velocity. The following papers can also be referred to for additional reading on the studies about mixed convection hybrid nanofluid flow (see [19–25]).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that mixed convection had proliferated the microorganism transfer rate and the y$y$‐direction flow velocity. The following papers can also be referred to for additional reading on the studies about mixed convection hybrid nanofluid flow (see [19–25]).…”
Section: Introductionmentioning
confidence: 99%
“…Analytical solutions to heat conduction issues with three different forms of periodic boundary conditions were discovered by Xu et al (2023), along with applications of these solutions. In their study conducted in 2023, Yahaya et al (2023) identified the presence of dual solutions throughout the computational process, instigating an investigation into the stability of the solution. The analysis correctly identified the first solution as stable and meaningful from a physical standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Fang and Jing [3] discovered the exact solutions in the unsteady rear stagnation point flow. The analytical and numerical study of the heat transfer and boundary layer flow in the unsteady flow of nanofluid may be obtained in Saidin et al, [4], Fathinia and Hussein [5], Yahaya et al, [6], and Xu et al, [7].…”
Section: Introductionmentioning
confidence: 99%